ENHANCE READING INTEREST IN DIGITAL ERA: PADALARANG PUBLIC LIBRARY - Amanda Ayuningtias, Dwitya
Indonesia is one of the developing countries with a low level of reading interest. Based on a study conducted by Central Connecticut State University in the United States, it was found that Indonesian reading interest rankings ranked 60th out of 61 countries. Indeed, the number of libraries in Indonesia reached 162,610 units in 2019 which places Indonesia as the country with the second largest library in the world, with the number one occupied by India. Thus, the problem of the low reading interest in Indonesia is not the quantity of library facilities, but the quality of the library that exists, which is a factor of comfort that makes visitors feel comfortable when they are in a library to read books. The importance of increasing the public's interest in reading will have an impact on the increase in the number of educated people and will be a first step in realizing the future of Indonesia as a developed country. In this era of digitalization, increased interest in reading can begin through the cultivation of lifestyle and reading habits in early childhood, the golden age of human character formation. From an architectural point of view, the answer to the problem of low reading interest in Indonesia is to improve the quality of the existing library space, not its quantity. A hybrid library that combines commercial functions and collaborates with CSR companies is a response to the issue of limited funding for the development of regional library facilities in Indonesia. The library also utilizes the potential of the industrial and agricultural sectors that exist in the West district of Bandung, such as the exploitation of anyaman industrial sector which is the largest industrial sector in Padalarang district as an external element of the building and the utilization of agricultural waste in creating environmentally friendly and robust library building materials. The cooperation of these sectors is a form of response in supporting the economy of the community around. However, the majority of quality libraries nowadays are located mostly in the capital of Jakarta, while there are many other areas that also need a quality library like the one in Jakarta.